RNF216 Regulates the Migration of Immortalized GnRH Neurons by Suppressing Beclin1-Mediated Autophagy - Li, Fangfang; Li, Dengfeng; Liu, Huadie; Cao, Bei-Bei; Jiang, Fang; Chen, Dan-Na; Li, Jia-Da (Frontiers in Endocrinology, 2019)
RNF216, encoding an E3 ubiquitin ligase, has been identified as a causative gene for Gordon Holmes syndrome, characterized by ataxia, dementia and hypogonadotropic hypogonadism. However, it is still elusive how deficiency in RNF216 leads to hypogonadotropic hypogonadism. In this study, by using GN11 immature GnRH neuronal cell line, we demonstrated an important role of RNF216 in the GnRH neuron migration. RNA interference of RNF216 inhibited GN11 cell migration, but had no effect on the proliferation of GN11 cells or GnRH expression. Knockdown of RNF216 increased the protein levels of its targets, Arc and Beclin1. RNAi of Beclin1, but not Arc, normalized the suppressive effect caused by RNF216 knockdown. As Beclin1 plays a critical role in the autophagy regulation, we further demonstrated that RNAi of RNF216 led to increase in autophagy, and autophagy inhibitor CQ and 3-MA rescued the GN11 cell migration deficit caused by RNF216 knockdown. We further demonstrated that pharmacological increase autophagy by rapamycin could suppress the GN11 cell migration. We thus have identified that RNF216 regulates the migration of GnRH neuron by suppressing Beclin1 mediated autophagy, and indicated a potential contribution of autophagy to the hypogonadotropic hypogonadism.